α-Adducin and Angiotensin I–Converting Enzyme Polymorphisms in Essential Hypertension - Clark, Catherine J.; Davies, Eleanor; Anderson, Niall H.; Farmer, Rosemary; Friel, Elaine C.; Fraser, Robert; Connell, John M. C. (Hypertension (Dallas, Tex. 1979), 2000)
This study focused on two genes that have previously been implicated in hypertension and may influence renal sodium handling, adducin, and angiotensin I–converting enzyme (ACE). We compared their polymorphic frequencies and interaction in patients with essential hypertension (n=128) and individually age- and gender-matched normotensive control subjects. The α-adducin G460W polymorphism was genotyped by DNA amplification and restriction digestion. The ACE I/D polymorphism was assayed by a triple-primer method, with a “nested” polymerase chain reaction primer situated completely within the insertion sequence of the I allele. The distributions of genotypes and alleles for the two polymorphisms were not significantly different between the case and control populations, and the cross-classification of cases by α-adducin and ACE genotype gave a distribution similar to that of control subjects. We have previously reported that the distributions of genotypes for two linked polymorphisms in the aldosterone synthase gene (one in the steroidogenic factor-1 [SF-1] binding site and the other an intronic conversion [IC]) were significantly different between this cohort of essential hypertensives and matched control subjects. The cross-classification of cases by α-adducin and SF-1, α-adducin and IC, ACE and SF-1, and ACE and IC genotype gave a distribution similar to that of control subjects. Hence, no evidence was found to suggest an association between either the α-adducin G460W or the ACE I/D polymorphism and hypertension in a careful case-control study. Furthermore, the α-adducin G460W, ACE I/D, and aldosterone synthase SF-1 and IC polymorphisms do not appear to interact in our hypertensive population.